A novel use of GPS for player`s movement analysis in Rugby Union - Iwabuchi, K.; Iwai, Y.; Furukawa, T. (7th World Congress on Science and Football (WCSF), 2011, 2011)
Introduction Descriptive approach by using GPS in Football code would suggest the concrete game-fitness factors. This study focuses on the movement characteristics of the Rugby Sevens which will held in 2016 Olympic games. In these days game analysis of rugby, the movement style is heterogeneous in the game between "Fifteens` games" and "Sevens` Games". Methods The analyzing method of the movement is based the concept in the game fitness by Global Positioning System and heart rate monitor for Japanese Sevens national team in 2010-2011. Results & Discussion Players` GPS and heart rate patterns were recorded. The increased frequency of "sprint running" would be suggest as the characteristics in Seven`s rugby games comparing with Fifteens` ones. The enhancement of "high-speed structure" of running would have concern with the tea tactics and training for the competition as the necessity physical condition. It would be the evidence that "Sevens" could be understood the heterogeneous with "Fifteens". Data of players` GPS would be cumulated and helped for the construction of standard of the tough runner for the competitive advantage and for the conditioning management. Conclusion The descriptive approach of the GPS movement analysis suggests an understanding the potential value structure on the football Science.